THE ROLE AND CONTRIBUTION OF CALLIGRAPHY IN ISLAMIC EDUCATION - Dea Adinda (Jurnal Eduslamic, 2024)
Calligraphy is a beautiful and attractive work of art and has Islamic nuances because it comes from Islamic religious knowledge, namely the Qur'an and hadits. Its existence is highly valued because it is an Islamic cultural heritage from ancient times to the present which can still be enjoyed for its beauty. Calligraphy has been widely taught in Islamic-based schools, especially Islamic boarding schools, because it is one of the arts that has a major role and contribution to Islamic education. The purpose of this study is to determine the role and contribution of calligraphy in Islamic education. This study uses the library research method, in which researchers conduct research by collecting data from various literature, including journals, books, theses, and others. The results of the study show that the art of calligraphy has a positive role and contribution in Islamic education, therefore the art of which is not only a medium of expression in Islamic education but also a well known propaganda medium. calligraphy is worthy of being passed on and introduced to Muslim generations for the sake of preserving Islamic culture.